2021
DOI: 10.3390/jcm10235563
|View full text |Cite
|
Sign up to set email alerts
|

Elderly People’s Access to Emergency Departments during the COVID-19 Pandemic: Results from a Large Population-Based Study in Italy

Abstract: Across the world, people have avoided seeking medical attention during the coronavirus pandemic, resulting in a marked reduction in emergency department (ED) visits. This retrospective cohort study examines in detail how the present pandemic affects ED use by the elderly. The regional database on ED visits in Veneto (northeastern Italy) was consulted to extract anonymous data on all ED visits during 2019 and 2020, along with details concerning patients’ characteristics (access mode, triage code, chief complain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Garaffa et al, in their recent study evaluating ED accesses during the first COVID-19 wave (February 2020 - June 2020), reported a decrease in accesses triaged as non-urgent compared to the same period in 2019 (p < 0.001) [7] . Bardin et al, considering only the elderly population (over 65 years) assessed during the first and second pandemic waves described substantial stability in non-urgent priority codes with comparable ED access rates between 2019 and 2020 (38.6% vs 37.0%) [21] . Analysis of individual months, however, shows that towards the end of the lockdown restrictions, non-urgent accesses begin to rise again, gradually tending towards pre-pandemic levels [7] , [21] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Garaffa et al, in their recent study evaluating ED accesses during the first COVID-19 wave (February 2020 - June 2020), reported a decrease in accesses triaged as non-urgent compared to the same period in 2019 (p < 0.001) [7] . Bardin et al, considering only the elderly population (over 65 years) assessed during the first and second pandemic waves described substantial stability in non-urgent priority codes with comparable ED access rates between 2019 and 2020 (38.6% vs 37.0%) [21] . Analysis of individual months, however, shows that towards the end of the lockdown restrictions, non-urgent accesses begin to rise again, gradually tending towards pre-pandemic levels [7] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Bardin et al, considering only the elderly population (over 65 years) assessed during the first and second pandemic waves described substantial stability in non-urgent priority codes with comparable ED access rates between 2019 and 2020 (38.6% vs 37.0%) [21] . Analysis of individual months, however, shows that towards the end of the lockdown restrictions, non-urgent accesses begin to rise again, gradually tending towards pre-pandemic levels [7] , [21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers concluded that COVID-19 related fears have resulted in fewer visits to the ED for emergent health conditions (18). A study from Italy also showed a 25.3% decrease in ED visits in 2020 compared to 2019, with the highest decrease in March 2020, by 52.4% (19). Similarly, a study from Taiwan witnessed a 33.4% decrease in non-traumatic ED visits during February to April 2020 compared to the same time frame of 2019 (20).…”
Section: Background/ Introductionmentioning
confidence: 93%